Economics Growth, Income Distribution, and Poverty in Central Java - Pramono Hariadi (Universitas Islam Indonesia, 2009)
Among the central issues in policy making are poverty alleviation and increasing income distribution.This paper measures the impact of economic growth on income inequality and poverty alleviation,namely whether income inequality becomes trade-off for poverty alleviation in 35 CentralJava regencies. The paper uses fixed effect model by weighting cross section weights. The resultsshow that economic growth increases income inequality. Furthermore, economic growth alleviatespoverty and increases income inequality, but the effect is smaller than the reduction in poverty.Therefore, the increased income inequality is not a trade off to poverty alleviation and the economicgrowth is effective to alleviate poverty.Keywords: Economic growth, income inequality, poverty alleviation